(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
Students’ self-education in modern conditions of society development, in the age of rapidly changing technologies and the acquisition of massive amounts of information, are dictated by increased requirements for the level of training of specialists in higher educational institutions. One of the most important indicators of professional competence of a specialist in the modern period of time is his ability to self-education. The transition to the formation of specialists of a wide profile, combining deep fundamental knowledge and thorough practical training, requires the activation of cognitive activity of students. Of particular importance is the formation of the need for active cognition and self-improvement of the individual, which requires its own sociological solution. This is due to the improvement of the mechanisms of social, economic and pedagogical management of universities, taking into account the human factor. The skillful use of the full potential of the educational process, the use of informal, creative means and methods of introducing students to values - all this makes humanitarian training a promising form of personal development of a future specialist